Sosialisasi Ergonomi Perkantoran Di SMK 10 Nopember Jakarta - Didi Junaedi; Diah Utami (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
Ergonomics is the relationship between work aspects such as work equipment, work procedures, work processes or systems, work environment with the physical, physiological, and psychological conditions of employees to adjust work aspects. Complex interactions between employee conditions that allow employees to work well, safely, comfortably, efficiently, and more productively. Factors that often cause danger when working in front of a computer are the frequency of typing and repetitive head movements from the keyboard to the monitor. The above dangers can affect the safety and health of workers in the administration or office sector. It is expected that SMK students majoring in Office Administration have knowledge and understanding the dangers of work in the office sector, and the importance of socialization regarding office ergonomics so that early prevention before entering the world of work regarding the dangers or potential injuries caused by office work. With this activity, it is hoped that they will gain an understanding of office ergonomics and students will be accustomed to avoiding bad activities that have an impact on health.